Kritik Hadis Prespektif Akram Diya' al-Umari - Badruz Zaman, Muhammad (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2018)
In the study of hadith criticism, there are two aspects that cannot be favored one of them. They are the criticism of sanad and the criticism of matan. Both of them have several validity criterias, they are the continuity of sanad, the narrators are reliable (‘ādil) and retentive (dābit), and free from the absurdity (shādh) and defect (‘illah). Many Muslim Scholars have formulated methods of hadith criticism. One of them Akram Diyā’ al-‘Umarī. Academically, this article examines Akram Diyā’  al-‘Umarī’s  thoughts on the hadith  criticism. He is a professor in the field on Islamic history and modern science. The background of Islamic historian adds to the options in the study of hadith criticism. He is a productive contemporary scholars. Many of his works were used as references by hadith researchers. One of his works that become masterpiece is Manhaj al-Naqd ‘ind al-Muhaddithin Muqaranan bi al-Manhaj al-Naqdi al-Gharbi (the Method of hadith criticism according to h}adith Scholars compared with Western criticism methods).